AN INVESTIGATION ON SAVINGS AND INVESTMENT BEHAVIOUR OF SALARIED WOMEN IN THOOTHUKUDI CITY (International Journal of Food and Nutritional Sciences, 2022)
Women all over the world face challenges and various hindrances in attaining financial security. Participation of women in the workforce may have increased, but they remain cautious and dependent on family members when it comes to managing their money. Many women manage money well, but we don't fully understand the challenges they face. This study aims to find out the level of awareness and preference towards savings and investment of women, and identify the factors that influence their decision-making process in Thoothukudi city. The researcher thus wanted to figure out how effective their money management strategies are and how these strategies contribute to their financial well-being. By doing this research, it is evident to offer insights that can help policymakers and others support women in making better financial choices.